THE RELIGIOUS VALUES IN TEACHING WRITING PERSUASIVE TEXT - Dewi Sartika; Rachmanita Rachmanita (Universitas Ahmad Dahlan)
Writing is sometimes neglected taught by the teacher due to the limitation of the time provided. Besides, in teaching writing, teacher tends to avoid the religious values in teaching writing persuasive text in order to build students’ character. However, students are required to master writing in order to express the idea or information in communication. Therefore, this study is an attempt to study the religious values in teaching writing persuasive text. The population of this study was all of the eleventh graders of SMA Negeri 1 Kandis Ogan Ilir. The samples were chosen by purposive sampling method. As a result, two classes consisting of thirty students in each classes were selected as the samples. The qualitative approach was used in this study and observation is the main instrument used to get the data about the process of teaching writing persuasive text. The observation done from the beginning to ending of teaching and learning process of writing persuasive text. Based on the observation, it was indicated that the students were interested in learning writing persuasive text and got some religious values to build their characters. In addition, the students were eager to write persuasive text because of interesting materials. They could explore their idea freely by writing the main information and writing information explaining the religious values in writing persuasive text. By teaching writing persuasive text including the religious values, hopefully the teacher of English can select the material and content of the subject matter which infused the religious values during the classroom.